The Study of Properties and Structure of Polylactide–Graphite Nanoplates Compositions. (31st May 2022) - Rogovina, Svetlana; Lomakin, Sergei; Usachev, Sergey; Gasymov, Miraga; Kuznetsova, Olga; Shilkina, Natalya; Shevchenko, Vitalii; Shapagin, Aleksey; Prut, Eduard; Berlin, Aleksander
Abstract : Composites of polylactide containing graphite nanoplates as a filler in the concentration range 1–20 wt% were prepared in methylene chloride using the sonication technique. The thermal characteristics and phase transitions were studied by DSC and TGA methods. The temperatures and heats of glass transition, crystallization, and melting were determined, and the degree of crystallinity during primary and secondary heating was calculated. It is shown that the introduction of graphite nanoplates leads to an increase in the elastic modulus and a decrease in the breaking stress and elongation at break. These changes are especially pronounced at 20% GNP content in the composition, when the corresponding mechanical parameters are characteristics of brittle polymer systems. The study of the electrical properties of the composites showed that the percolation threshold in these materials is close to 7 wt%, which is significantly lower than in the case of spherical particles of comparable density. The SEM study of the filled composites showed a system of pores, which were apparently formed during the evaporation of solvent in the process of their preparation. Diverse structures of PLA/GNP composites films after hot pressure were established by the SEM method.